Updates in Gastroesophageal Reflux Disease Management: From Proton Pump Inhibitors to Dietary and Lifestyle Modifications - Jakov Ivan Bucan; Tamara Braut; Antea Krsek; Vlatka Sotosek; Lara Baticic (Gastrointestinal Disorders, 2025)
Gastroesophageal reflux disease (GERD) is a common chronic gastrointestinal disorder that greatly influences patients’ quality of life and represents a growing public health concern. Characterized by typical and atypical symptoms, GERD encompasses a range of clinical phenotypes and is associated with complications such as erosive esophagitis and Barrett’s esophagus. This review intends to provide a thorough overview of current scientific knowledge on the etiological factors, risk determinants, and pathophysiology of GERD, while exploring diagnostic challenges and therapeutic approaches. Proton pump inhibitors (PPIs) remain the mainstay of medical therapy; however, concerns regarding their long-term safety have encouraged interest in adjunctive and alternative strategies. Emerging pharmacological agents, plant-based treatments, and integrative approaches rooted in traditional medicine offer promising modalities for enhanced management. Additionally, dietary and lifestyle modifications such as weight control, meal timing, and avoidance of trigger foods, are essential components of effective care. A multidisciplinary framework incorporating pharmacological, nutritional, and behavioral strategies is emphasized as the most reliable path toward personalized and sustainable GERD management. This review further aims to synthesize current therapeutic modalities and evolving perspectives in the treatment of GERD.